Embodying the Qur'an. Issue 1 (24th June 2019) - Wilkens, Katharina
Abstract : Mohammed was said by his wife Aisha to be a "walking Qur'an". This saying is taken both as a statement of his exemplary character as well as an image for the fact that he embodied the words of the Qur'an. Memorization and recitation from memory is conceived of as embodying the holy text and it is also the primary aim of Qur'anic education. In West Africa, drinking the ink of the writing boards is the closing ritual of a lesson at Qur'anic school, the text being thus embodied both mentally and physically. Drinking the Qur'an, literally incorporating its words infused in water, is also widely considered to be an effective medicine, in which materiality and sonality of the sacred words contribute to its efficacy. In my paper, I will take up the notion of embodying and sounding the Qur'an as an aesthetic ideology governing its ritual uses.